Răspuns :
6•(1+2+3+...+60):2•(1+2+3+...+60)=
6•(60•61:2):2•(60•61:2)=
6•(3660:2):2•(3660:2)=
6•1830:2•1830=
10980:3660=3
6•(60•61:2):2•(60•61:2)=
6•(3660:2):2•(3660:2)=
6•1830:2•1830=
10980:3660=3
(6 + 12 + 18 + ... + 360) : (2 + 4 + 6 +... + 120) =
6(1 + 2 + 3 +... + 60) : 2(1 + 2 + 3 +... + 60) =
6 * [60 * (60+ 1) : 2] : 2 * (60 * (60 + 1) : 2] =
6 * 30 * 61 : 2 * 30 * 61 =
6 : 2
3
6(1 + 2 + 3 +... + 60) : 2(1 + 2 + 3 +... + 60) =
6 * [60 * (60+ 1) : 2] : 2 * (60 * (60 + 1) : 2] =
6 * 30 * 61 : 2 * 30 * 61 =
6 : 2
3